Mobbing process as a psychosocial risk factor in educational groups - Victoria N. Chaika; Vladislav A. Mashtakov; Olga S. Matorina; Oleg V. Streltsov; Oksana G. Meretukova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The socio-psychological phenomenon of mobbing in educational groups requires a detailed study and identification of new factors and dependencies. The purpose of this study is to analyze statistical information, identify the features of the formation and development of the mobbing process in the student team, and develop relevant techniques for timely response at any stage of the mobbing process. The article discusses the results of research by domestic and foreign authors on the problems of mobbing. A brief overview of the history of the term is given. Participants are identified and the main prerequisites for the formation of the mobbing process are identified. In accordance with the stages of formation and development of mobbing as a socio-psychological phenomenon, the stages in the structure of the mobbing process in educational groups are defined. A diagram of the relationship between objects and subjects of the mobbing process is presented. Based on the analysis, a standard version of the actions of a potential victim of mobbing has been developed. The article considers the mobbing process as a factor that negatively affects the moral and psychological climate of educational groups. The lack of a psychologically healthy climate in the educational team leads to a reluctance to work in a team and a possible decrease in the effectiveness of perception of educational material and involvement in the educational process. The authors note the need to use techniques for timely response at any stage of the mobbing process. An attempt is made to develop tools for potential victims of the mobbing process in educational groups in order to resolve a conflict situation at any stage of the process.